An Overseas Chinese Author on Chineseness: A Study of Catherine Lim’s Novels - Kasempat Poolsawas (Asiatic: IIUM Journal of English Language and Literature, 2023)
The objectives of this documentary research are to study Catherine Lim’s concept of Chineseness in the Chinese diasporic context as well as to investigate the identity and existence of the ethnic culture of the Chinese diaspora in the Straits Settlement. This study is analyzed through Lim’s three novels: The Bondmaid (1995), The Teardrop Story Woman (1998), and The Song of Silver Frond (2003). All the novels present stories of the Straits Chinese or the Chinese diaspora in the Straits Settlement, the territories under the British occupation in the age of colonisation. The findings reveal that Lim’s cultural and social upbringing in Straits Chinese society helped mold her as a female diasporic Chinese. Straits Chinese society in Lim’s novels is one that adheres to Chinese beliefs and cultural norms as well as their cultural roots. However, Lim still reflects how the context of displacement from the motherland becomes an important factor to dilute the sense of Chineseness among the Straits Chinese. Moreover, Lim also interestingly presents the images of Chinese diasporic women in various dimensions in her novels.